SHERPA and Institutional Repositories - Hubbard, Bill (United Kingdom Serials Group, 2003)
The SHERPA project (Securing a Hybrid Environment for Research Preservation and Access) has been set up to encourage change in the scholarly communication process by creating open-access institutional "e-print" repositories for the dissemination of research findings. This article looks at the terminology involved with such repositories and at the issues that such repositories raise for their construction and use. It reviews the advantages of having an institutional basis for a repository and identifies the key issues that have arisen so far in project work.